Alpha lipoic acid attenuates iron induced oxidative acute kidney injury in rats. (18th August 2021) - Cavdar, Zahide; Oktan, Mehmet Asi; Ural, Cemre; Kocak, Ayse; Calisir, Meryem; Heybeli, Cihan; Yildiz, Serkan; Ozbal, Seda; Arslan, Sevki; Ergur, Bekir Ugur; Yilmaz, Osman; Cavdar, Caner
ABSTRACT: Iron has been implicated in oxidative tissue injury owing to its ability to generate reactive oxygen species (ROS). We investigated the reno-protective effects of alpha lipoic acid (ALA) by investigating its effects on the kidney isoform of NADPH oxidase (Nox4) and the specific signaling pathways, p38 MAPK and PI3K/Akt, which participate in apoptosis and survival, respectively. We established four groups of seven rats: control, 100 mg/kg ALA, 80 mg/kg iron sucrose (IS) and IS + ALA. IS and ALA were injected intravenously and rats were sacrificied after 6 h. The mRNA expression of the subunits of NADPH oxidase, Nox4 and p22phox; tumor necrosis factor-alpha (TNF-α); and kidney injury molecule-1 (KIM-1) were measured using quantitative real time polymerase chain reaction (qRT-PCR). Active caspase-3 protein expression was evaluated by immunostaining. Also, p38 MAPK and PI3K/Akt signaling pathways were analyzed using western blot. ALA suppressed the mRNA expression of Nox4, p22phox, TNF-α and KIM-1. Active caspase-3 protein expression induced by IS was decreased by ALA. ALA also suppressed p38 MAPK and activated the PI3K/Akt signaling pathway following IS administration. We found that ALA may be an effective strategy for preventing oxidative acute kidney injury caused by IS.